Tonga : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Tonga. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses recent economic developments, economic outlook, risks, and challenges in Tonga. The Tongan economy has been rebounding since a contraction in FY2013. Growth accelerated from 2.1 percent in FY2014 to 3.7 percent in FY2015, supported by construction, tourism, strong remittances, and strong private credit, notwithstanding weather-related disruptions to agricultural production. The FY2016 real GDP growth is projected to remain relatively strong at 3.1 percent, driven by a recovery in agriculture and an increase in construction activity in preparation for the South Pacific Games. However, a protracted period of slower growth in advanced and emerging market economies, particularly in Australia and New Zealand, could weigh on Tonga via aid, remittances, and tourism channels.